The role of the right premotor cortex and temporo-parietal junction in defensive responses to visual threats. (November 2019) - Sagliano, Laura; Vela, Maria; Trojano, Luigi; Conson, Massimiliano
Abstract: Previous neuroimaging studies demonstrated that several brain areas are involved in detecting threats and activating defensive responses to threatening stimuli. The right premotor cortex (PM) is mainly activated during freezing, whereas the right temporoparietal junction (TPJ) is involved in attentional orienting towards threat. The aim of the present study was to test the possibility to modulate attentional orienting and defensive responses to threatening stimuli by interfering with the activity of the right TPJ and PM with cathodal. The results demonstrated that after sham stimulation the participants were slower to respond to threatening than to non-threatening stimuli, consistent with the idea that the experimental paradigm induced a freeze-like response to threatening stimuli. Active tDCS over PM reversed this response pattern, whereas TPJ stimulation wiped out the difference between responses to threatening and non-threatening stimuli. Our findings demonstrated that inhibitory stimulation of PM favours active defensive responses to threatening stimuli whereas TPJ inhibitory stimulation reduces attentional prioritizing of threatening stimuli. In conclusion, our study showed that it is possible to modulate responses to threatening stimuli by interfering with activity of at least two cortical regions of the brain network involved in dealing with threats.